(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This thesis examines the dynamics of bilateral and multilateral cooperation between India and the United States of America against the background of global geopolitical changes in recent years, the important directions identified in the development of mutual relations, and the impetus for strengthening cooperation. It is dedicated to the analysis of the main factors and existing shortcomings, the expected prospects for the relations between the two countries.